SERAPAN FOSFOR TANAMAN JAGUNG MANIS (Zea mays saccharata Sturth) AKIBAT PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK SP-36 PADA ENTISOLS SIDERA - Syarifudin Syarifudin; Yosep S. Pata’dungan; Isrun Isrun (Agroland: Jurnal Ilmu-ilmu Pertanian, 2020)
The objectives of the research were to determine the effect of chicken manure and SP-36 fertilizer and their interaction on the phosphorous uptake and yield of sweet corn (Zea mays saccharata Sturth) and to determine the optimum rates of the chicken manure and the SP-36 fertilizer for maximal sweet corn production.  The research was conducted in Sidera, Sigi Biromaru subdistrict, Sigi district of Central Sulawesi province from July to October 2018.  The research was arranged in a two-factorial randomized block design. The first factors was chicken manure rates i.e. 0 ton ha-1 (P0), 10 ton ha-1 (P1), 25 ton ha-1 (P2), and 40 ton ha-1 (P3). The second factors was SP-36 fertilizer rates i.e. 0 kg ha-1 (S0), 100 kg ha-1 (S1), 200 kg ha-1 (S2), and 300 kg ha-1 (S3). The addition of 40 ton ha-1 chicken manure and 300 kg ha-1 SP-36 fertilizer resulted in highest soil pH (6.38), total soil P (52.53 mg 100 g-1), available soil P (28.87 ppm), plant dry weight (714 g plant-1), phosphorous uptake (0.68 g plant-1) and corn cob weight (6.45 ton ha-1). Keywords: Chicken Manure, Entisols, Phosphorus Uptake, SP-36, and Sweet corn.